Strategi Dakwah KUA Dalam Meningkatkan Keberagamaan Masyarakat Tigabinanga Karo - Ayu Meilisa Berutu (STAI Bumi Silampari, 2026)
This study aims to analyze the da’wah strategy implemented by the Office of Religious Affairs (KUA) in improving the religious quality of the Muslim community in Tigabinanga, Karo Regency. This research is based on the social context of Tigabinanga as a multicultural area where Muslims live as a minority community within strong local cultural and interreligious relations. This study used a descriptive qualitative method. Data were collected through observation, in-depth interviews, and documentation involving KUA officers, religious counselors, community leaders, and local residents. The findings show that KUA Tigabinanga applies four main da’wah strategies: mapping the socio-religious conditions of the community, delivering religious guidance gradually, applying a cultural approach, and utilizing digital media. These strategies are grounded in Qur’anic principles of da’wah, namely bil al-hikmah, mau’izhah hasanah, and mujadalah billati hiya ahsan. The study also reveals that KUA functions not only as an administrative institution but also as a religious mentor, social mediator, and promoter of religious moderation. The strategy has contributed to strengthening religious understanding, social harmony, and community participation in religious activities.